2018
DOI: 10.1101/447540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Analysis of Single Nucleotide polymorphisms (SNPs) in Human TCell Acute Lymphocytic Leukemia Protein 1 (TAL1) Gene/Comprehensive Study

Abstract: Background: TAL1 is a proto-oncogene whose distorted modifications in committed T-cell Precursors is related with the development of T-ALL, it also found to be related to many other human hematological diseases such as lymphoblastic lymphoma, immunodeficiency 18, acute myeloid leukemia and diamond-blackfan Anemia. Objectives: This study aims to predict the effect of nsSNPs on TAL1 protein structure function Methods: Retrieved nSNPs in the coding and 3'UTR regions were analyzed using different in silico tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies in the past have conducted various analysis particularly in-silico analysis that combines bioinformatics tool to predict the structural and functional consequences of nsSNPs occurring at the coding region of the genome. One study conducted SNP analysis in TAL1 gene which is a proto-oncogene hence is found associated with various hematological diseases 13 . Another study performed computational analysis on glycoprotein M6A that identified nsSNPs which are damaging to the structure and function of the protein 14 .…”
mentioning
confidence: 99%
“…Numerous studies in the past have conducted various analysis particularly in-silico analysis that combines bioinformatics tool to predict the structural and functional consequences of nsSNPs occurring at the coding region of the genome. One study conducted SNP analysis in TAL1 gene which is a proto-oncogene hence is found associated with various hematological diseases 13 . Another study performed computational analysis on glycoprotein M6A that identified nsSNPs which are damaging to the structure and function of the protein 14 .…”
mentioning
confidence: 99%